Komunikacja marketingowa detalicznych przedsiębiorstw handlowych w Polsce. Wyniki badań prowadzonych metodą ocen ekspertów - Marek Drzazga (Studia i Materiały)
At the turn of the XXth and XXIst century the importance of marketing communication in marketing activities of companies has grown considerably. The aim of the research was to estimate the importance of marketing communication in marketing policy of retail trade companies functioning on Polish market. The research focused specifically on the identification of crucial factors of the retail trade companies’ surroundings determining the process of their marketing communication, as well as on identification and establishing the importance of the marketing communication tools. The identification of contemporary marketing processes carried out by retail trade companies and the role they play in marketing communication is also in the scope of the present research. The research was carried out by means of an expert method from mid-September up to the end of November 2010 in Poland. In the research a group of 46 experts (both theoreticians and practitioners) in the field of marketing, retail trade and marketing communication was addressed.